(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Lichen sclerosus (LS) is a disease of unknown cause that results in white patches on the skin, which may cause scarring on and around genital skin1. Several risk factors have been proposed, including autoimmune diseases, infections and genetic predisposition2,3. There is evidence that LS can be associated with thyroid disease4. Women are more commonly affected than men (10 to 1 ratio), particularly prepubertal girls and after menopause. The condition most commonly occurs on the vulva and around the anus with ivory-white elevations that may be flat and glistening. There may be marked itching or the condition may be without any symptoms. There may also be thinning and shrinkage of the genital area. This condition is presented here as an younger woman presented with acute form of lichen sclerosus. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 47-50